Tratamentos endodônticos realizados em uma clínica de graduação: características dos casos, prevalência de fraturas de instrumentos e percepção dos alunos - Luiza Cruz Guimarães (2020)
The study evaluated the endodontic treatments performed in the Endodontic clinics of UFMG School of Dentistry. This is a cross-sectional study that analyzed the previous urgent procedures, the completion of the cases, the prevalence of fractures of endodontic instruments and the perceptions of students regarding such occurrence and endodontic practice. Data were obtained through clinical records and during clinical practice during eighteen months between the years of 2017 and 2018. Students' perceptions were raised through the application of a questionnaire. Data were analyzed in a descriptive way by absolute and relative frequency and bivariate analysis performed using the Pearson's ChiSquare test with Bonferroni correction considering a 95% confidence level and 5% significance probability (p≤0, 05) in SPSS v. 22. The molars (p> 0.0001) and the teeth diagnosed with pulp necrosis (p <0.0001) were the most related to previous emergency procedures. 85.9% of endodontic treatments were completed. Treatments were less finalized in adolescents compared with young people (p = 0.006) and older adults (p = 0.003), in molar teeth compared with anterior teeth (p = 0.005) and premolars (p = 0.003), in teeth that had previous emergency treatments (p = 0.002) and in patients who missed appointments (p = 0.014). Instrument fractures occurred in 3.9% of cases in curved canals of molar teeth (66.7%). Fragments were located in the coronal/middle third (61.3%), measuring more than three millimeters (72.2%) and removed or exceeded in half of the occurrences. Most students reported controlling the number of uses (88.9%) and in 66.7% of fractured occurred in up to the third use. Students reported difficulties (98.0%), most technical procedures (54.1%) and to the morphology and location of teeth (26.8%). For students who did not report the occurrence of fractures, the majority reported that their interest (88.2%) and confidence (83.9%) would not be influenced in case of a fracture. Among the students who had the fracture experience, a decrease in this percentage was observed, 44.5% and 33.3% respectively. The study showed a satisfactory number of completed treatments requiring few sessions. The conclusion was associated with the anatomical complexity of the molars, the low age of the patients and absenteeism. The prevalence of fractures of endodontic instruments was low. The aspects related to them suggest torsional overload as the most likely cause. The most related difficulties are the lack of technical skills or the anatomical complexity of the molars. The perception of their own confidence and interest in the specialty seems to be directly affected by the occurrence of instrument fractures.